Inoculating rhizome-propagated Sporobolus pumilus with a native mycorrhizal fungus increases salt marsh plant growth and survival - Tyler W. d'Entremont; Juan C. López-Gutiérrez; Allison K. Walker (Canadian Science Publishing, 2021)
Salt marshes are ecosystems of significant ecological importance for coastal stability and fundamental roles in marine ecosystems. Salt marshes are declining due to anthropogenic and natural causes including sea level rise. Coastal restoration efforts have increased worldwide, but many fail in long-term coastal stability. We used a naturally occurring arbuscular mycorrhizal fungus (AMF) to test whether survival and early growth of the salt marsh grass Sporobolus pumilus (formerly Spartina patens) improved under simulated salt marsh conditions. Using a tidal mesocosm bench, we grew inoculated plants with varying AMF treatments under simulated tidal regimes to determine if AMF could aid in establishment of healthy Sporobolus communities. Rhizome-derived S. pumilus had greater survival and grew faster than seed-derived plants. Plants inoculated with propagated AMF consistently outperformed both sterile and native sediment controls in terms of plant survival and growth. Use of rhizome-derived Sporobolus inoculated with propagated Funneliformis geosporum showed the most promise in producing successful plant populations for salt marsh restoration. This may be due to plant life stage and improved plant nutrient status, allowing rhizome-derived plants to grow more quickly than seed-derived plants. Using these plants in future large-scale restoration may increase re-establishment of salt marsh ecosystems.